Analysis of cancer perception by elderly people - Braz, Isaac Felipe Leite; Gomes, Raquel Andresa Duarte; Azevedo, Mariele Silva de; Alves, Francisco das Chagas Marison; Seabra, Danilo Silveira; Lima, Francisco Pignataro; Pereira, Joabe dos Santos (Einstein (São Paulo, Brazil), 2018)
ABSTRACT Objective To evaluate the perception of elderly population about cancer, correlating it with the clinical variables sex, age and past history of cancer. Methods The sample was composed of 300 individuals, 174 (58%) women. A questionnaire containing ten questions and based on the Health Information National Trends Survey was used. For statistical analysis, a p value <0.05 was considered significant. Results Individuals aged 80 years and older were more likely to believe that regular tests can identify cancer in early stages, compared to elderly aged under 80 years (OR: 0.103; CI95%: 0.021-0.499; p=0.005). Elderly subjects with positive history of cancer were more likely to believe that few people survive cancer, compared to those who never had the disease (OR: 0.379; CI95%: 0.167-0.858; p=0.02). All patients with a positive history of cancer believed that early-detected cancer can be cured. Conclusion Aged individuals with ≥80 years or older believed in regular exams as a form of early detection of cancer, probably due to the greater frequency of medical instructions. Subjects who had cancer believed that few people survive the disease, perhaps because of the negative experiences they have experienced. Considering the greater presence of fatalistic perceptions, this group constitutes a potential target for educational approaches about cancer. RESUMO Objetivo Analisar a percepção do câncer pela população idosa, correlacionando os dados obtidos com as variáveis clínicas de sexo, idade e histórico pessoal de câncer. Métodos A amostra foi composta por 300 idosos, sendo 174 (58%) do sexo feminino. Foi aplicado um questionário de dez questões baseado no Health Information National Trends Survey, com questões relacionadas à percepção do câncer. Para a análise estatística, o valor de p<0,05 foi considerado significativo. Resultados Indivíduos com idade acima de 80 anos demonstram chance maior de acreditar que os exames regulares podem identificar o câncer em estágios iniciais, se comparados aos idosos com menos idade (OR: 0,103; IC95%: 0,021-0,499; p=0,005). Os idosos que tiveram câncer exibiram chances maiores de acreditar que poucas pessoas sobrevivem ao câncer, em relação àquelas que nunca tiveram a doença (OR: 0,379; IC95%: 0,167-0,858; p=0,02). Todos os pacientes com histórico positivo de câncer revelaram acreditar que o câncer detectado cedo pode ser curado. Conclusão Idosos com ≥80 anos acreditam nos exames regulares como forma de descobrir a doença no início, provavelmente pela maior frequência de orientações médicas. Indivíduos que tiveram câncer acreditam que poucas pessoas sobrevivem à doença, talvez pelas experiências negativas que vivenciaram. Por exibir mais chances de percepções fatalistas, este grupo se configura como alvo em potencial para abordagens educativas acerca do câncer.